Frequency regulation in alternation-current transports across metal to insulator transitions of thin film correlated perovskite nickelates. (10th June 2023) - Li, Haifan; Meng, Fanqi; Bian, Yi; Zhou, Xuanchi; Wang, Jiaou; Xu, Xiaoguang; Jiang, Yong; Chen, Nuofu; Chen, Jikun
Highlights: The origin of frequency dependence in the impedance of typical metal to insulator transition (MIT) materials such as Re NiO3 and VO2 are demonstrated. Apart from the sudden change in the impedance modulus across MIT temperature ( T MIT ) similar to the DC transport, the MIT also triggers abrupt variation in the impedance phase. By regulating frequency, the thermistor function of Re NiO3 and VO2 can be transformed among NTCR (10 2 –10 4  Hz), delta TCR (10 4 –10 6  Hz), and PTCR (10 6 –10 7  Hz). The MIT enables sharper temperature dependence of impedance across T MIT compared to the situation with the absence of MIT within the investigated range of temperature. A materials design method to meet the needs of applicable temperature by designing T MIT of materials is proposed. Abstract: Although the metal to insulator transition (MIT) observed in d-band correlated metal oxides enables promising applications (e.g., correlated logical devices and Mottronic devices), its present recognition is mainly limited on the direct current (DC) electrical transports. Up to date, the MIT from the perspective of alternation current (AC) transport and its potential electronic applications remains yet unclear. Herein, we demonstrate the frequency ( f AC ) dependence in the impedance ( Z   =   Z'+iZ'' ) of typical MIT materials, such as thin film rare-earth nickelates ( Re NiO3 ), across the critical MIT temperature ( T MIT ). Apart from the abrupt change in the impedance modulus (| Z |) across the critical temperature ( T MIT ) similar to the DC transport, the MIT also triggers non-continuous variation in the impedance phase ( θ ), and this enables the f AC -regulations in the Z'-T tendencies ( Z' =| Z |cos θ ). At the critical f AC range (e.g., 10 4 –10 6  Hz), the conversing variations in | Z |- T and cos θ - T across T MIT result in non-monotonic delta-shape Z'-T tendency in Sm x Nd1- x NiO3, the full width half maximum of which is effectively narrowed compared to the situation with the absence of MIT. Further imparting lower or higher f AC elevate the domination in | Z |- T and cos θ - T, respectively, but also enables abrupt Z'-T tendencies across T MIT showing negative temperature coefficient of resistance (NTCR) or positive temperature coefficient of resistance (PTCR). By introducing f AC as a new freedom, the MIT behavior can be more comprehensively regulated electronically, and this extends the vision in exploring the new electronic applications based on the correlated MIT materials from the AC perspective. Graphical Abstract: Image, graphical abstract